The influence of underground coal mining on groundwater in Barapukuria and its adjoining areas, Northwest Bangladesh - Hasibul Zahan; Anwar Zahid; Md Sakaouth Hossain (Discover Geoscience)
Abstract This study evaluates the water quality and hydrogeological assessment for domestic use, irrigation, and drinking near the Barapukuria coal mine area. The groundwater table data from 2010 to 2021 revealed that it reached its lowest point (8.0 to 11.0 m) pre-monsoon and its highest (3.0 to 6.0 m) post-monsoon. The concentrations of major anions and cations, and the values of EC, DO, TDS, pH, and salinity, were found within the acceptable and allowable limits for all purposes, except for a small amount of Fe2− and HCO3 −, when conducting field investigation and laboratory analysis. Numerous noteworthy analyses were carried out, including Piper's trilinear diagram, US salinity chart, Durov diagram, and Wilcox diagram. The weathering of silicates, specifically crystalline dolomitic limestone and Ca-Mg silicates, is responsible for the dominance of ions in the sequence Na+ > Mg2+ > Ca2+ > K+. Alkali-earth metals and weakly acidic anions are present, like early groundwater reserves, as the dominance of Na-K-HCO3 and Mg-HCO3 and less recently recharged water of Ca-HCO3, which has a mixed anion and cation dominance and temporary hardness. The computed values of TDS, EC, SAR, TH, PI, and CAI indicate excellent to good quality water and are acceptable for all purposes with a few anomalies in Na% (64.99 meq/L), MH (59.02 meq/L), and RSC (144.11 meq/L). Changes in groundwater quality and level are gradually lowering as mining continues, falling below the suction limit (> 7.5 m) for hand tube wells (HTWs) and eventually because groundwater is being used for power plants. Regular surface and groundwater quality and level monitoring is recommended around the mine area.